Preparation and synthesis mechanism of ytterbium monosilicate nano-powders by a cocurrent coprecipitation method. Issue 10 (July 2020) - Wu, Nan-nan; Wang, Ya-lei; Liu, Ru-tie; Liu, Huai-fei; Liu, Rong; Li, A-xin; Xiong, Xiang
Abstract: In this study, nano-sized Yb2 SiO5 powders were prepared by a cocurrent coprecipitation method. The influence of Si/Yb molar ratio and calcination temperature on the phase composition and structure of Yb2 SiO5 were investigated, and the synthesis mechanism of Yb2 SiO5 was also discussed. Results indicated that the Si/Yb molar ratio has a significant influence on the phase composition of Yb2 SiO5 powders. Under nonstoichiometric conditions, trace of Yb2 O3 and Yb2 Si2 O7 will be formed as impurities in the as-prepared Yb2 SiO5 powders. In addition, the elevated calcination temperature can promote the formation of stable X2-Yb2 SiO5 . During the synthesis process, a -[Si-O-Yb]- network structure was formed in the Yb2 SiO5 precursors, which resulted from the in-situ replacement of Si by Yb atoms. The -[Si-O-Yb]- network will transformed to a X1-Yb2 SiO5 firstly during the calcination process. With the calcination temperature increased, the metastable X1-Yb2 SiO5 can convert to a stable X2-Yb2 SiO5 gradually through a reconstructive process. Yb2 O3 and Yb2 Si2 O7 may also be formed during the reconstructive process of X1-Yb2 SiO5 .